Aerospace series. Screws, pan head, offset cruciform recess, coarse tolerance normal shank, long thread, in alloy steel, cadmium plated. Classification: 1 100 PMa (at ambient temperature)/235 °C. (8th November 2019) - British Standards Institution,
No abstract available